User perception of the benefits of neo-vernacular architecture in selected art and cultural centres in Lagos - Jegede, Foluke Oladunni; Enwonwu, Chiagozie Mitchelle (Frontiers in Built Environment, 2025)
The success of any architectural space depends on how users perceive and experience it, particularly in arts and cultural centres, which serve as hubs for cultural expression, engagement, and tourism. These centres must reflect local architectural identity to ensure long-term cultural relevance and contribute meaningfully to sustainability goals. This study examines users’ perceptions of the benefits of neo-vernacular architecture in selected arts and cultural centres in Lagos, addressing a gap in comparative evaluations through a quantitative analysis of perceived contributions to cultural, environmental, economic, and social sustainability. Out of 120 distributed questionnaires, 110 valid responses were collected across three centres: John Randle Centre, Terra Kulture, and KAP Hub. Data analysis using the Kruskal–Wallis H test and descriptive statistics revealed that while users generally perceive neo-vernacular architecture as beneficial across cultural, economic, environmental and social dimensions, variation exists in how these benefits are expressed across contexts. The findings highlight the need to align traditional architectural expression with sustainability, with future research incorporating objective performance metrics to complement perception-based insights.